Christian Teachings on Social Justice: An Analytical Study - Dr. Muhammad Riaz Mahmood (Journal of Religion and Society, 2026)
This analytical study explores the concept of social justice within Christian theology, examining its doctrinal foundations, historical development, and contemporary relevance. The research begins by establishing the importance and background of the topic, followed by a conceptual analysis of social justice, its scope, and modern applicability. It investigates the intrinsic relationship between religious teachings and social justice, arguing that they are inseparably linked. The core of the study delves into specific Christian teachings, analyzing the Christian concept of God, prophethood and the pivotal role of Jesus Christ as exemplars of justice. Further, it examines the contributions of Church fathers, the role of Christian worship, ethics, rituals, education, and parables in fostering a just society. The study also confronts the socio-political challenges facing Christianity today and concludes with an analysis of the Christian concept of punishment and its implications for restorative justice. The findings reveal that social justice is not a peripheral theme but is central to Christian identity, demanding active engagement in the struggle against oppression, poverty, and inequality, thereby offering a comprehensive framework for societal reform. Keywords: Bible, Christianity, Church, Ethics, Jesus Christ, Prophethood, Social Justice, Societal Reform, Theology.